Local History Learning Based on Family History - Candra Permana; Didin Saripudin; Nana Supriatna; Leli Yulifar (Universitas Hamzanwadi, 2026)
There remains a stigma that history learning is perceived as boring and merely recounts dates, figures, and places of historical events. Students’ low interest in history subjects is reflected in their limited participation, such as lack of motivation to study history, weak reading skills, and minimal engagement in asking or answering questions posed by teachers during classroom lessons. Therefore, this study was conducted to examine history learning at the senior high school level. The objectives are to explore students’ perceptions and interest in history, to describe family-based local history learning as an engaging and meaningful alternative, and to explain its benefits for students. The research method employed is a literature review, with sources collected from ebooks and articles. The findings indicate that family-based local history learning can serve as an engaging and meaningful alternative to traditional history instruction. The conclusion emphasizes that meaningful and engaging history learning begins with creative teachers who are able to design and implement lessons that allow students to truly experience the benefits of studying history.